Factors Contributing to Substance Abuse among Kaimosi Friends University Students, Vihiga Kenya - Okanga, Anne; Musungu, Joseph; Amugitsi, Lilian (International Journal of Psychology, 2025)
Purpose: Substance abuse among university students is a global public health concern, largely due to their vulnerability during the transition to independence, with serious implications for personal growth and national development. The goal of the study was to investigate the contributing factors to substance abuse among students at Kaimosi Friends University (KAFU). Methodology: A descriptive cross-sectional design was used where a total of 350 undergraduate students were selected through stratified random sampling, and data were collected in May 2025 using a structured questionnaire adapted from NACADA. Analysis was conducted thematically and using SPSS version 25. Ethical approval was obtained from MMUST, and confidentiality and informed consent were upheld. Findings: The study revealed that social media was the main source of information on substance abuse. A significant portion of students (65%) frequently experienced stress or anxiety, with 50% using substances as a coping mechanism. Academic pressure, perceived unfair grading, and personal issues were major stressors. Peer influence was notable, with 55% having friends who used drugs and 45.1% reporting peer encouragement to try substances, although some emphasized personal choice. Easy access to substances (60%) and media glorification of drug use (50%) were also reported. Family influences played a role, with 55.1% citing substance use by fathers or brothers and others noting emotional neglect and family challenges. The study concluded that substance abuse at KAFU is driven by a complex set of interconnected factors. Unique Contribution to Theory, Practice and Policy: It recommends strengthening mental health services, promoting peer education, advocating for family engagement, controlling substance availability, and creating a supportive academic environment to mitigate the issue.